Generation of a synthetic GlcNAcylated nucleosome reveals regulation of stability by H2A-Thr101 GlcNAcylation - Lercher, Lukas; Raj, Ritu; Patel, Nisha A.; Price, Joshua; Mohammed, Shabaz; Robinson, Carol V.; Schofield, Christopher J.; Davis, Benjamin G. (Nature Communications, 2015)
O-GlcNAcylation is a newly discovered histone modification implicated in transcriptional regulation, but no structural information on the physical effect of GlcNAcylation on chromatin exists. Here, we generate synthetic, pure GlcNAcylated histones and nucleosomes and reveal that GlcNAcylation can modulate structure through direct destabilization of H2A/H2B dimers in the nucleosome, thus promoting an ‘open’ chromatin state. The results suggest that a plausible molecular basis for one role of histone O-GlcNAcylation in epigenetic regulation is to lower the barrier for RNA polymerase passage and hence increase transcription.